TEST 88 Dark and Light Triad Traits, Age, and Female Teacher Well-Being – A Parallel Mediation Analysis - Orosova, Olga; Liptakova, Janka; Gajdosova, Beata (European Journal of Mental Health, 2026)
Introduction: Despite its importance, teacher well-being remainsunderexplored, particularly regarding teacher-related traits. Identifyingfactors that shape well-being across career stages, especially the relationshipbetween well-being and age, is essential.Aim: The aim of the present study is to examine the association between age,a set of Dark and Light Triad traits, and female teacher well-being indicators.Methods: 1,114 female teachers (mean age = 46, SD = 9.12) completed anonline, self-reported questionnaire which included the Short Dark Triad Scale,the Light Triad Scale, and the Teacher Subjective Well-being Questionnaire.Confirmatory factor analysis, Pearson’s correlation, hierarchical regression,moderation, and mediation analyses were carried out.Results: The mediation analysis showed a significant direct effect of older ageon higher school connectedness (β = .11, p < .001, 95% CI [.05, .16]) andon higher teaching efficacy (β = .18, p < .001, 95% CI [.13, .23]). Age waspositively associated with narcissism, which in turn enhanced both teachingefficacy and school connectedness, as well as with Faith in Humanity, whichcontributed to higher school connectedness. Conversely, lower levels ofHumanism were associated with reduced teaching efficacy.Conclusions: The current study highlights key findings on the relationshipsbetween age, Dark Triad and Light Triad traits, and teacher well-being,showing that Narcissism (Dark Triad) and Faith in Humanity or Humanism(Light Triad) significantly mediated the associations between age and schoolconnectedness and teaching efficacy, thereby offering insights into areasnecessary to improve well-being throughout female teachers’ careers.